Tlingit potlatch dancers in costume, Klukwan, Alaska, ca. 1898 - Hegg, Eric A., 1867-1948
Seven men and a boy in beaded and embroidered shirts, hats and headdresses, ca. 1897-1900. They have painted faces, hold feathers, and several wear noserings. Caption on image: Klukwan. 881. Potlatch dancers. E. A. Hegg